Andean bear (Tremarctos ornatus) population density and relative abundance at the buffer zone of the Chingaza National Natural Park, cordillera oriental of the Colombian Andes - Rodríguez, Daniel (2020)
The Andean bear (Tremarctos ornatus) population density and relative abundance within the Chingaza Massif were assessed between September 2015 and May 2016. One hundred seventeen (117) camera traps were installed at 9 grids: 13 cameras per grid, each camera separated 750 m from the other; the sampling effort was 17,057 days-trap. Two thousand seven hundred eighty-four (2,784) native fauna records were obtained, 1,456 corresponding to mammals, 183 records for Andean bear specimens, 158 of them independent bear records (at least one hour between records), and 106 effective-independent bear records (also permitting individual recognition). Fifty-seven (57) Andean bear individuals were identified according to key external morphological features. Sixteen (16) adults were recaptured (12 males and 4 females), with a maximum mean distance of 27.22 km. Bears population density was 2.9 bears per 100 km². Based on this density and the buffer area of the sampling grids, we estimated an overall number of 122 bears in 4,215.15 km². The estimated density is the first for the species in Colombia and the lowest regarding previous reports from other countries. Thus, it is necessary to better understand how integral habitat quality and the anthropic impacts on habitat quality, availability, and connectivity may affect the Andean bear population densities in Colombia, as a useful tool for assessing populations` state and focus future conservation actions.